Implementasi Metode Cerita dalam Meningkatkan Kemampuan Berbahasa Anak Usia Dini - Sururin, Anis; Umkabu, Talabudin; Faisal (Indonesian Journal of Teaching and Teacher Education, 2023)
This article explores the ways in which teachers develop young children’s language skills. An overview of early childhood language skills, the implementation of the story method in learning and the implication of the story method on children’s language skill are analysed in depth. Using qualitative description, this study obtained data through observation, interviews, and documentation. This is done systematically to allow data collection in this qualitative research could explain what has been observed. The result of this study indicated that the use of the story method or storytelling in improving early childhood language skills in the learning process is carried out by teachers systematically. Therefore, not only early childhood language skills are improved, but also social interaction. The active involvement of early childhood in learning is a benefit that could be perceived by the parents of learners. The consideration of digital media in the story method is a concept that needs to be explored specifically in order to make the implementation of learning methods more diverse and further improve early childhood abilities.